2016
DOI: 10.1155/2016/5760139
|View full text |Cite
|
Sign up to set email alerts
|

Game Models on Optimal Strategies in a Tourism Dual-Channel Supply Chain

Abstract: This paper explores a two-echelon tourism supply chain consisting of a hotel and an online travel agency. The upside hotel rooms can be sold through the downside hotel alliance and online travel agency. The hotel alliance, selling rooms at a lower price, is a direct sale platform with a negligible entry fee. Notwithstanding, the online travel agency sells the room at a higher price with related personalized service. Customers will be refunded partially in case of their cancellation or no-show. An integrated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In terms of dual-channel pricing decisions based on the Bertrand game and the Stackelberg game, the article [50] analysed efficient pricing decisions by comparing dynamic and static dual-channel supply chain pricing models. These models are mostly based on the relevant factors that influence supply chain decisions such as price [51] and service [52].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of dual-channel pricing decisions based on the Bertrand game and the Stackelberg game, the article [50] analysed efficient pricing decisions by comparing dynamic and static dual-channel supply chain pricing models. These models are mostly based on the relevant factors that influence supply chain decisions such as price [51] and service [52].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ere are a large number of research studies on the traditional dual-channel supply chain in which a manufacturer has an online channel and the retailer has a physical store channel. ese research studies on the dualchannel supply chain focus on channel selection [13][14][15][16], channel coordination [13,[17][18][19][20], the pricing and other decisions optimization [21][22][23][24][25][26][27], and channel competition [28][29][30]. A comprehensive review of dual-channel supply chains can be found in Tsay and Agrawal [11] and Cai et al [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find that the TOs would bid a lower wholesale room price to the hotel with higher capacity and vice versa. Yang et al (2016) discuss a two-echelon tourism supply chain consisting of a hotel and an online travel agency by comparing the sequential game with price competition. Long and Shi (2017) investigate the optimal pricing strategies of a tour operator and an online travel agency when they adopt the Online To Offline (O2O) model through the online sale and offline service cooperation.…”
Section: Pricing In the Tourism Industrymentioning
confidence: 99%